Nonparametric Pointwise Estimation for a Regression Model with Multiplicative Noise. (11th October 2021) - Chen, Jia; Kou, Junke
Abstract : In this paper, we consider a general nonparametric regression estimation model with the feature of having multiplicative noise. We propose a linear estimator and nonlinear estimator by wavelet method. The convergence rates of those regression estimators under pointwise error over Besov spaces are proved. It turns out that the obtained convergence rates are consistent with the optimal convergence rate of pointwise nonparametric functional estimation.